Modelling of photovoltaic-thermal collectors for the provision of electricity and low temperature heat—Comparison of different flow rate control approaches to optimize the electrical yield. (June 2021) - Christ, Daniel; Kaltschmitt, Martin
Highlights: Locally adapted flow rate control approaches can increase the electrical yield of PVT collectors by up to 2.80%. Compared to a reference case, an increase in additional electrical yield of up to 27% is possible. Constant flow rate control approaches provide a flat distribution of temperature increase. Variable flow rate control approaches provide a distribution peak of temperature increase. Abstract : Photovoltaic-thermal (PVT) collectors can provide heat and electricity. A quasi-stationary model of a PVT collector is presented and validated based on measured data. Subsequently, the electrical and thermal performance of such a collector is simulated for different locations. These simulations focus on different flow rate control approaches with the aim of maximizing the electrical yield. The simulation results show that the two control approaches presented in this paper have the potential to increase the electrical output for all locations. The increase in additional electrical output at locations with higher solar radiation is significantly higher than the increase in solar radiation between the locations investigated. Additionally, the cooling fluids' temperature differences for such PVT collectors vary between the investigated control approaches, where variable flow rates lead to a steadier increase in cooling fluids' temperature. In conclusion, the flow rate needs to be adopted to the pre-defined main goal of the respective PVT collector. The use of variable flow rates by providing low-temperature heat at a more constant temperature level appears to be advantageous in this context.